KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL DAN PERILAKU INDIVIDU TERHADAP KINERJA PEGAWAI DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN KLUNGKUNG - I Gede Suyasa Swastika (Jurnal Manajemen dan Bisnis, 2014)
The purpose of this study is : 1 To determine the effect on the behavior of individualintelligence intellectual in the Department of Population and Civil Registration Klungkung 2 )To determine the effect of emotional intelligence on the behavior of individuals in theDepartment of Population and Civil Registration Klungkung 3 ) To determine the effect on thebehavior of spiritual intelligence individuals in the Department of Population and CivilRegistration Klungkung 4 ) To determine the effect of individual behavior on the performanceof employees in the Department of Population and Civil Registration Klungkung .Respondents of this study of employees in the Department of Population and CivilRegistration Klungkung totaling 56 people . Collecting data in this study using a questionnairecontaining 21 questions , each question using 10 alternative answers . Analysis of the dataused to answer research questions and test the statistical methods used path analysis withAMOS software version 20The results showed that : 1 ) Intelligence intellectual is positive and significant effecton the behavior of individual employees , the better intelligence employees the better thebehavior of individual employees of the Department of Population and Civil RegistrationKlungkung , 2 ) Emotional intelligence is positive and significant effect on the behavior ofindividual employees , the better emotional intelligence employees the better the behavior ofindividual employees of Population and Civil Registration Klungkung , 3 ) Spiritualintelligence is positive and significant effect on the behavior of individual employees , the betteran employee spiritual intelligence of Population and Civil Registration Klungkung , the betterthe behavior of individual employees 4 ) the behavior of individual positive and significanteffect on the performance of employees , it means that the better the behavior of individualemployees of the Department of Population and Civil Registration Klungkung , the better theperformance of employees .Keywords : intellectual, emotional intelligence , spiritual intelligence , individual behaviorand performance of employees